Functionalization of steel surfaces with organic acids: Influence on wetting and corrosion behavior - Alonso Frank, Micael; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2017)
Self-assembled monolayers (SAMs) have been used to tailor surface properties of different metal surfaces. Typically SAMs can be bound to surface hydroxyls of a thin oxide layer that forms on the surface of a less noble metal and dominates its properties. The effects of SAMs with different anchoring groups and chain lengths regarding wettability, corrosion resistance and homogeneity of the layer were studied in detail. Alkyl carbonic and phosphonic acids were selected to create a hydrophobic layer on the surface of stainless steel ASIS 316L and on carbon steel N80. SAMs were formed by dip-coating of the samples in an organic acid ethanolic solution. Sum frequency generation (SFG) analysis together with contact angle and electrochemical measurements were carried out to explore correlations between tailored wettability, corrosion resistance, and layer homogeneity on one side, and the chain length, anchor group, concentration and immersion time on the other side. The homogeneity of the layers as well as the resulting surface hydrophobicity increased with an increase of the immersion time, the contact angle reached a maximum (ca. 120°) for an immersion time of approximately 2 days.
Keywords: Carbon steel N80; Hydrophobicity; Myristic acid; Octadecylphosphonic acid (ODPA); Stainless steel 316 L; Stearic acid; Sum frequency generation; Surface functionalization

Indentation and Self-Healing Mechanisms of a Self-Assembled Monolayer-A Combined Experimental and Modeling Study - Meltzer, Christian; Paul, Jonas; Dietrich, Hanno; Jäger, Christof; Clark, Timothy; Zahn, Dirk; Braunschweig, Björn; Peukert, Wolfgang (Journal of the American Chemical Society, 2014)
A combination of in situ vibrational sum-frequency generation (SFG) spectroscopy and molecular-dynamics (MD) simulations has allowed us to study the effects of indentation of self-assembled octadecylphosphonic acid (ODPA) monolayers on α-Al2O3(0001). Stress-induced changes in the vibrational signatures of C-H stretching vibrations in SFG spectra and the results of MD simulations provide clear evidence for an increase in gauche-defect density in the monolayer as a response to indentation. A stress-dependent analysis indicates that the defect density reaches saturation at approximately 155 MPa. After stress is released, the MD simulations show an almost instantaneous healing of pressure-induced defects in good agreement with experimental results. The lateral extent of the contact areas was studied with colocalized SFG spectroscopy and compared to theoretical predictions for pressure gradients from Hertzian contact theory. SFG experiments reveal a gradual increase in gauche-defect density with pressure before saturation close to the contact center. Furthermore, our MD simulations show a spatial anisotropy of pressure-induced effects within ODPA domains: molecules tilted in the direction of the pressure gradient increase in tilt angle while those on the opposite side form gauche-defects.
Keywords: spectroscopy; monolayer; self-assembly

Lubrication of Individual Microcontacts by a Self-Assembled Alkyl Phosphonic Acid Monolayer on α-Al2O3(0001) - Paul, Jonas; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang (Langmuir, 2016)
We report on the tribological behavior of a self-assembled alkyl phosphonic acid monolayer on the microscale using the colloidal probe technique. Friction-load data and adhesion forces were measured with borosilicate glass particles on uncoated and octadecylphosphonic acid (ODPA) coated α-AlO(0001) surfaces. A significant decrease in friction force was observed after surface coating, while the adhesion force was only moderately reduced. We assume the lubrication effect of the ODPA self-assembled monolayer (SAM) to be close to the maximum obtainable of alkyl phosphonic acids in the studied system due to the high molecular order which was confirmed by vibrational sum-frequency generation. At small loads, a nonlinear dependence of friction force to load was maintained after surface coating. However, a shift from a contact behavior well described by the DMT model toward the JKR model occurred that is possibly related to the altered elastic properties of the coated surface. With increasing load, a linear friction-load behavior was observed on the coated samples. Molecular plowing and adhesive interactions were identified as responsible mechanisms. In all friction experiments, we could not detect any wear neither of the colloidal probes nor at the surfaces of uncoated and coated samples. This proves the high wear resistivity of the studied ODPA SAM.

Molecular structure of octadecylphosphonic acids during their self-assembly on α-Al2O3(0001) - Meltzer, Christian; Yu, Hui; Peukert, Wolfgang; Braunschweig, Björn (Physical Chemistry Chemical Physics, 2018)

Self-Assembled Monolayers Get Their Final Finish via a Quasi-Langmuir-Blodgett Transfer - Meltzer, Christian; Dietrich, Hanno; Zahn, Dirk; Peukert, Wolfgang; Braunschweig, Björn (Langmuir, 2015)
The growth of self-assembled monolayers (SAMs) of octadecylphosphonic acid (ODPA) molecules on α-Al2O3(0001) and subsequent dewetting of the SAMs were studied with a combination of in situ sum-frequency generation (SFG) and molecular dynamics (MD) simulations. Although SAM growth after deposition times >8 h reduces to nearly negligible values, the resultant ODPA SAMs in solution are still not in a well-ordered state with the alkyl chains in all-trans configurations. In fact, in situ SFG spectroscopy revealed a comparatively high concentration of gauche defects of the SAM in the ODPA 2-propanol solution even after a growth time of 16 h. Here, results of the MD simulations strongly suggest that defects can be caused by ODPA molecules which are not attached to the substrate but are incorporated into the SAM layer with the polar headgroup oriented into the 2-propanol solvent. This inverted adsorption geometry of additional ODPA molecules blocks adsorption sites and thus stabilizes the SAM without improving ordering to an extent that all molecules are in the all-trans configuration. While persistent in solution, the observed defects can be healed out when the SAMs are transferred from the solvent to a gas phase. During this process, a quasi-Langmuir-Blodgett transfer of molecules takes place which drives the SAM into a higher conformational state and significantly improves its quality.